Etiological classification and management of dizziness in children: A systematic review and meta-analysis - Zhang, Jifang; Zhu, Qi; Shen, Jiali; Chen, Jianyong; Jin, Yulian; Zhang, Qing; Duan, Maoli; Yang, Jun (Frontiers in Neurology, 2023)
Background: Dizziness in children that could not be diagnosed at the early stage in the past are becoming increasingly clear to a large extent. However, the recognition of the diagnosis and management remains discrepant and controversial due to their complicated and varied etiology. Central and peripheral vestibular disorders, psychogenic and systematic diseases, and genetic pathogeny constitute childhood etiological entity. Further understanding and the prevalence of vertigo disorders is of crucial importance. Methods: This systematic review and meta-analysis were conducted through systematically searching for literatures on childhood vertigo disorders published up to May 2022. Literatures were evaluated by strict screening and diagnostic criteria. Their quality was assessed using the Agency for Healthcare and Research Quality (AHRQ) standards. The test for homogeneity was conducted to determine the fixed effects model or random-effect model employed. Results: Twenty-three retrospective cross-sectional studies involving 7647 children with vertigo disorders were finally included, with an AHRQ score greater than 4 (high or moderate quality). Our results demonstrated that peripheral vertigo (52.20%, 95% CI: 42.9%-61.4%) was more common in children than central vertigo (28.7%, 95% CI: 20.8%-37.4%), psychogenic vertigo (7.0%, 95% CI: 4.8%-10.0%), and other systemic vertigo (4.7%, 95% CI: 2.6%-8.2%). The five most common etiological diagnoses associated with peripheral vertigo included benign paroxysmal vertigo of childhood (BPVC) (19.50%, 95% CI: 13.5%-28.3%), sinusitis-related diseases (10.7%, 95% CI: -11.2%-32.6%), vestibular or semicircular canal dysfunction (9.20%, 95% CI: 5.7%-15.0%), benign paroxysmal positional vertigo （BPPV） (7.20%, 95% CI: 3.9%-11.5%) and orthostatic dysregulation (6.8%, 95% CI: 3.4%-13.0%). Vestibular migraine (20.3%, 95% CI: 15.4%-25.2%) was the most seen etiological diagnosis associated with central vertigo in children. In addition, we found the sex-based difference influenced the outcome of psychogenic vertigo and vestibular migraine, while there was no significant difference in other categories. For the management of vertigo, symptomatical management is the first choice for the most types of vertigo disorder in pediatrics. Conclusion: Complex etiology and non-specific clinical manifestations of vertigo in the pediatrics are challenging for diagnoses. Reliable diagnosis and effective management depend on the close cooperation of multiple disciplines, combined with comprehensive consideration of the alternative characteristics of vertigo in children.